Development of Digital-Based Constructivistic Teaching Materials to Improve the Metacognitive Ability of Disaster Materials Students - Ade Irwansah; Bambang Sigit Widodo; Sukma Pradana Prasetya (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze students' metacognitive abilities and the effectiveness of digital-based constructivist teaching materials. It was done to improve students' metacognitive abilities. This study's method was an experiment with a quantitative approach. In this study, the pretest-posttest control group design was used. The ADDIE model was then used to create teaching materials. The MAI (Metacognitive Awareness Inventory) questionnaire instrument was used to assess students' metacognitive abilities. The treatment was provided to the experimental class by using digital-based constructivist teaching materials in the learning process. The aim is to improve students' metacognitive knowledge and skills. The independent sample t-test SPSS version 20.0 for windows was used to compare the two average values (pretest and posttest of the experimental class with the control class). The researchers then used the effect size test to determine the efficacy of digital constructivist teaching materials. It is for improving students' metacognitive abilities. The results of this study showed 1) From the total results of the validation assessment by experts and teachers of geography subjects, the final percentage of 86.5 percent was said to be feasible and valid to be tested. 2) As metacognition improves, so did the value of the metacognition test, which now had a gain index of 57.59%, which translates to